2008
DOI: 10.1002/ajpa.20875
|View full text |Cite
|
Sign up to set email alerts
|

Greater sciatic notch as a sex indicator in juveniles

Abstract: Using Schutkowski's method for juvenile sex determination (Schutkowski H. 1993. Am J Phys Anthropol 90:199-205), we evaluated the morphology of the greater sciatic notch of 56 ilia (23 females and 33 males) from a documented skeletal collection housed at the Bocage Museum in Lisbon (Portugal). After applying Schutkowski's original methodology and comparing the results with previous studies, we used age-adjusted metrical variables to describe greater sciatic notch depth, breadth, and angle. Although results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 24 publications
6
56
1
14
Order By: Relevance
“…The individual was aged by dental development, eruption, and formation using the Ubelaker chart [47] and primary ossification centres [47,48]. Sex of a subadult is difficult to estimate [49][50][51] and the methods proposed do not produce highly reliable results. Using the morphology of the symphyseal region of the mandible [52] and the shape of the mandible [53] in combination with the robusticity of long bones [54], the shape of the sciatic notch would have been used to aid in determining sex; however, the majority of the pelvis is missing.…”
Section: Methodsmentioning
confidence: 99%
“…The individual was aged by dental development, eruption, and formation using the Ubelaker chart [47] and primary ossification centres [47,48]. Sex of a subadult is difficult to estimate [49][50][51] and the methods proposed do not produce highly reliable results. Using the morphology of the symphyseal region of the mandible [52] and the shape of the mandible [53] in combination with the robusticity of long bones [54], the shape of the sciatic notch would have been used to aid in determining sex; however, the majority of the pelvis is missing.…”
Section: Methodsmentioning
confidence: 99%
“…The finding is also close to that presented by Musgrave (7), who did not take into account the bone shrinkage: "full-term fetus or neonate (of 38-39 intrauterine weeks by modern standards)." Some authors have observed sexual dimorphism in juvenile skeletal samples of known sex (24,25), whereas other authors suggest that the application of this method to archaeological and forensic skeletal material may be problematic (26). Thus, given the uncertainty of the results, no sex determination attempts have been made to this individual.…”
Section: Significancementioning
confidence: 99%
“…His methods, originally developed on an 18th-19th century population from London (Christ Church, Spitalfields), were later tested by Sutter [11] on a Chilean population of immature mummies and revealed a comparatively consistent result (79.0-80.7% success). Nonetheless, more recent tests on a different population have placed doubt upon the reliability of the criteria proposed by Schutkowski [9], suggesting that the general applicability of his methods is hampered by a lack of precision in the definition of features and the subjective nature of the scoring procedures [12,13].…”
Section: Introductionmentioning
confidence: 99%